Analisis Film Tilik (Ladies On Top) Menggunakan Teori Kineikonic Andrew Burn - Muhammad Nanda Restu Subkhi; Ucik Ana Fardilla (JURNAL RUPA, 2021)
"Tilik Ladies on Top" is a movie without cheap erotic scenes and surprisingly is a short movie. This movie shows that Indonesian movie goers might enlarge their taste proven by tenth millions views on You Tube. This research uses the Kineikonic model analysis. The purposes of the research is to determine Embodied Modes, Visual Modes, Auditory Modes of " Tilik Ladies on Top. The purpose of this study was to determine the aspects that build the movie, such as facial expressions, costumes, make-up, set design, lighting, and shooting. The results of this study describe the continuity between the narrative and cinematic aspects of the film. This film is able to present local culture with the use of language.